Death due to postural asphyxia caused by severe drunkenness - case report - Miljković, Milica; Vujović, Maja; Kostić, Emilija; Antović, Aleksandra; Pinterović, Bogdan; Pančić, Dimitrije; Milić, Miroslav (Archives of Pharmacy, 2022)
Postural asphyxia is a type of suffocation that occurs when a person remains in a non-physiological position for an extended time, so the abdominal organs pressure on the diaphragm and impaired adequate respiratory movements. An autopsy of a male person aged 42 years found beside the road was performed on demand of the investigative authorities'. The body was in an upside-down position with the legs arched over the head and chest. External autopsy findings revealed livid discoloration of the head, neck, shoulders, and chest, as well as minor bruises and abrasions of the scalp and extremities. Internal autopsy examination detected swelling of the brain and lungs, blood stasis in the internal organs, and petechial pleural and pericardial bleeding. Pathohistological examination of the organs revealed blood stasis and cerebral edema. Toxicological-chemical analysis of samples of blood, urine, and vitreous fluid using the technique of "head space" gas chromatography with an ionizing flame detector proved the presence of ethyl alcohol in concentrations: 2.85 mg / mL (2.70 ‰), 44 mg / mL (3.39 ‰), and 3.18 mg / mL (3.16 ‰), retrospectively. It was concluded that the death was violent, resulting from suffocation caused by postural asphyxia in the state of severe drunkenness.